Effect of the skill, gender, and kick order on the kinematic characteristics of underwater undulatory swimming in the dorsal position - Veiga, S.; Qiu, X.; Trinidad, A.; Dolek, B. E.; De la Rubia, A.; Navarro, E. (Journal of Human Kinetics, 2024)
Backstroke swimmers display the greatest contribution of underwater kicking during the swimming race distances, but, surprisingly, there is little evidence of how kicking kinematics in the dorsal position should be performed. The aim of the present study was to examine the kinematic characteristics of competitive swimmers during underwater undulatory swimming in the dorsal position, with special attention to the swimmers` gender, the level of skill, and kick order. Forty-one national-level swimmers (27 females and 14 males) were filmed from an underwater lateral view while performing a 25-m backstroke from a push start, and they were divided into fast and slow groups according to their kicking velocity. Direct linear algorithms were employed to reconstruct the two-dimensional kinematic characteristics of the first and final kicks of the underwater section. There were no differences between males and females in kicking performance when data were normalised to the swimmers` height. However, swimmers in the fast-kicking group were distinguished by a greater kicking frequency (n²: 0.15) and specific segmental kinematics related to a lower knee range of motion. Swimmers decreased kicking velocity (n²: 0.47) in addition to the kicking frequency (n²: 0.31) and length (n²: 0.16), but increased the kicking amplitude (n²: 0.11) between the first and the final kicks. Changes in kicking segmental kinematics were more related to modification in body orientation during the underwater trajectory than to the kicking motion itself. These results provide the first solid evidence of how swimmers should kick for better performance in dorsal underwater swimming.